2000
DOI: 10.1155/s1023621x00000257
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelasticity in Turbomachines: Some Aspects of the Effect of Coupling Modeling and Blade Material Changes

Abstract: Two methods are generally used for the aeroelastic analysis of bladed-disc assemblies. The first, often referred to as the energy method, assumes that the fluid does not modify invacuum structural dynamic behavior. On the other hand, the second, based on an eigenvalue approach, considers the feedback effect of the fluid on the structure. In this paper, these methods are compared using different test cases, in order to highlight the limitations of the energy method. Within this comparison, the effect of materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…-model of thin shells [2,3]; -model of a thin plate with variable thickness [4]; -model of vibrations of the blade taking into account the spatial shape of the blade [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-model of thin shells [2,3]; -model of a thin plate with variable thickness [4]; -model of vibrations of the blade taking into account the spatial shape of the blade [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…For this problem, the most suitable model is the model of blade vibrations taking into account the spatial shape and material, since it allows taking into account both the design of the blade and the uneven temperature and properties. There are several solutions for this model, including the modal approach [5,6] integration of the equations of motion [7]. The modal approach consists in finding a solution in the form of a linear combination of the eigenmodes of vibration of the blade, the coefficients of which depend on time and are calculated at each time step.…”
Section: Introductionmentioning
confidence: 99%
“…At the present day, the 2-D approach is verified by tests of cylindrical blades (i.e., blades whose cross section is constant along the span) [18][19][20][21][22][23][24]. A study [25] is devoted to the comparison of energy and modal methods based on a quasi-3-D approach. It is shown that, for sufficiently stiff metal blades, the energy method gives results very close to those obtained by the modal method, but for a more flexible composite blades, the inaccuracy of the energy method, caused by the difference of the mode shapes in the flow and in vacuum, is more pronounced.…”
Section: Introductionmentioning
confidence: 99%